PENGARUH EXTERNAL FINANCING NEEDS DAN OWNERSHIP STRUCTURE TERHADAP KINERJA PERUSAHAAN PERBANKAN - Elfride Hanum Simanjuntak; Aditya Septiani (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to examine the effect of external financing needs and ownership structure on banking performance. The dependent variable in this study is banking performance measured by using Tobin’s Q. The independent variables in this study are external financing needs and ownership structure which consists of managerial ownership and institutional ownership. In addition, company size, leverage and return on assets (ROA) are used as control variables. This study uses a sample consisting of 187 banking companies listed on the Indonesia Stock Exchange during the 2014-2018 period. Sampling was done by using purposive sampling technique with certain criteria. This research method uses multiple linear regression analysis. The results of this study indicate that external financing needs has a negative and significant effect on banking performance and institutional ownership has a positive and significant effect on the performance of banking companies. While managerial ownership does not affect banking performance.